Group Decision Support System Fuzzy Profile Matching Method With Organizational Citizenship Behaviour - Putu Sugiartawan; I Made Yudiana; Paholo Iman Prakoso (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
The most important thing that can be done by the company, namely the employee selection process, in order to guarantee the right candidate in the right position as well with value-form Organizational Citizenship Behavior. In this study. The methods that can be applied in the career path process in an organization. By implementing a group decision support system, where the opinions of several decision-makers can be accommodated, as well as in problem-solving and communication occurs in a group. This study uses the profile matching method because it can provide an assessment of the potential of each employee candidate by comparing the employee's personal profile with the profile of the position in question, combined with fuzzy logic so that the original value obtained by the alternative remains consistent from the beginning to the ranking process. The results obtained in the form of ranking reports using the Borda method, based on calculations from the fuzzy profile matching method, are expected to help company organizations to facilitate the promotion process.